Northern Russian Names of Flour and Bread Made of Different Varieties of Grain: The Semantic-Motivational Aspect - Ksenia Viktorovna Osipova (Известия Уральского федерального университета. Серия 2: Гуманитарные науки, 2021)
This article discusses dialectal names of bread made of a mixture of two or three varieties of flour (barley, rye, oat, or wheat), recorded on the territory of Arkhangelsk, Vologda, and northern Kostroma regions. The author carries out an analysis of this group of vocabulary in linguo-geographic and semantic-motivational aspects in order to determine the peculiarities of the formation of the lexical group under consideration and the corresponding food tradition, to identify possible foreign language and foreign cultural influences and the etymological reconstruction of lexemes with an unclear motivation. There are several groups of names and areas of distribution of the ideogram “bread made of mixed flour”. It is established that the use of bread made of mixed flour was typical of residents of the south, southeast, and west of Arkhangelsk region, the central and eastern parts of Vologda region, and the northeastern parts of Kostroma region. The author singles out several types of names and areas of their distribution, i.e. двоежиток — троежитник; двинянка; соричник, сорица; смёш, смешечник; сутолока. Referring to the semantic-motivational models revealed, the author proposes an etymology for the northern Russian двинянка ‘bread that has two layers of dough’ in connection with the number два ‘two’. Given the existing etymology of Rus. dial. сорник ‘bread made of several types of flour’ in connection with the Komi сор ‘admixture’, it is proposed to consider dial. смешенник as a calque of loanwords with the root сор- (сорник, etc.). The archaic nature of the vocabulary group in question makes it possible to consider the tradition of making mixed flour and bread out of it quite old. It was partially borrowed by Russian peasants from the Finno-Ugric peoples who had more experience in baking bread from barley.